Use of cytogenetic techniques and flow cytometry to characterize the yacon genome (Acta Scientiarum. Agronomy, 2025)
Yacon (Smallanthus sonchifolius), a tuberous root native to the Andean region, is cultivated in various countries and is valued as a functional and medicinal food due to its nutraceutical properties. These properties include probiotic, antidiabetic, antioxidant, and antimicrobial effects, which contribute to its beneficial impact on human health. Despite this, the genetic diversity of yacon, which significantly influences trait expression and phenotypes, remains poorly explored. To date, only the number of chromosomes in the karyotype has been reported. This study, therefore, aimed to measure the nuclear genome size, determine the chromosome number, and characterize the karyotype of different yacon genotypes. For the first time, this research presents the karyogram and calculates the 2C nuclear value of yacon genotypes cultivated in a tropical environment outside the Andean region. This analysis is particularly significant as genetic material can be influenced and altered by environmental conditions. Our findings aim to identify such potential variations. The karyotype was characterized by 29 pairs of chromosomes: 13 submetacentric (1–5, 7–12, 14, 20) and 16 metacentric pairs (6, 13, 15–19, 21–29), with sizes ranging from 3.64 to 1.67 Î¼m and secondary constriction in chromosome pair 21. Moreover, the karyotype presented a chromosome number of 2n = 58, contrasting with individuals of yacon cultivated in tropical environments, which presented a chromosome number of 2n = 32. The average 2C DNA content found was 2C = 6.39 pg, corroborating previous reports that presented relative variations from 2C = 5.82 to 6.12 pg. The observed genome 1C = 3,124.710 Mbp was considered small. Our methodology successfully obtained prometaphase and metaphase chromosomes, free of cytoplasmic traits and without overlaps. This study enriches the fundamental genetic knowledge of yacon, contributing to its conservation, evolution, and diversification, and affecting its agricultural potential beyond the Andean regions.